Republic of Kazakhstan : Evaluation of National Tuberculosis and HIV/AIDS Programs - World Bank (Washington, DC, 2012)
Tuberculosis (TB) and HIV/AIDS have a significant impact on the economy and society of Kazakhstan and a growing challenge to the country's health system. Together these two diseases could severely constrain the future economic growth and the human capital development of the country. To face the challenge of the dual threat of HIV/AIDS and TB focused, highly cost-effective programs will be required to ensure that limited resources produce the highest impact. To this end, this study addresses the overall performance of the tuberculosis, human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) programs in Kazakhstan. This paper provides a detailed analysis of the efficiency, quality, and effectiveness of each of the programs and identifies the structure of financing and cost-effectiveness. It focuses on the availability of resources to combat the diseases and the distribution of these resources within the country. (See related World Bank Technical Paper, "Stopping TB in Central Asia: Priorities for Action.") Also, the report identifies opportunities to improve performance, specifically analyzing the relationship between inputs and outcomes and highlighting, in the case of the TB Program, opportunities to produce significant savings or improved value-for-money in the program. The executive summary presents an overview of the study, summarizing the key findings and recommendations. The second section under each program then outlines the key issues and actions associated with the performance of the national programs. The key actions summarize recommendations on future areas of interest that would complement the findings of this report and deepen policymakers' understanding of how to improve the system.